ANALISIS KETERAMPILAN BERBICARA SISWA MELALUI PEMBUATAN TEKS DESKRIPTIF DI KELAS IV SD NEGERI 101340 BATANG BARUHAR JULU TAHUN AJARAN 2023/2024 - Kumala Sari, Rani; Ilahi, Afdhal; Ningtyas, Rani Kusuma; Nurbaiti, Nurbaiti (Jurnal Ilmiah Pendidikan Dasar (JIPDAS), 2025)
This research aims to analyze students' speaking skills through the creation of descriptive texts in Grade IV of State Elementary School 101340 Batang Baruhar Julu during the academic year 2023/2024. This study employs a qualitative descriptive approach, utilizing data collection techniques such as interviews, observations, and document analysis. The results indicate significant improvement in students' speaking skills. Out of a total of 20 students, 80% demonstrated clear pronunciation, 70% spoke fluently, 85% showed good comprehension of the content discussed, 95% were able to construct sentences effectively, and 85% exhibited good argumentative abilities. Student-centered approaches, open discussions, and direct demonstrations by teachers regarding the characteristics of flowers proved highly effective in enhancing students' descriptive writing skills. Teachers encouraged students to relate their writing to personal experiences, provided clear guidelines, and supported the revision process with constructive feedback. Students were motivated to write about flowers due to curiosity and personal memories. They also endeavored to compose easily understandable texts, incorporate personal experiences, and regularly revise their writing. Overall, this research demonstrates that the majority of students have shown progress in various aspects of speaking skills. However, there is still room for further improvement. Additional support from teachers and appropriate learning activities are crucial to strengthening each aspect of students' speaking skills and preparing them for more complex communication in the future.